Acceptability and feasibility pilot randomised controlled trial of medical skin camouflage for recovery of women prisoners with self-harm scarring (COVER): the study protocol. Issue 1 (17th January 2019) - Mitchell, Heather; Abel, Kathryn M; Dunlop, Brendan James; Walker, Tammi; Ranote, Sandeep; Robinson, Louise; Edgar, Fiona; Millington, Tracy; Meacock, Rachel; Shaw, Jenny; Gutridge, Kerry
Abstract : Introduction: Self-harm in prison is a major public health concern. Less than 5% of UK prisoners are women, but they carry out more than a fifth of prison self-harm. Scars resulting from self-harm can be traumatising and stigmatising, yet there has been little focus on recovery of women prisoners with self-harm scarring. Medical skin camouflage (MSC) clinics treat individuals with disfiguring skin conditions, with evidence of improved well-being, self-esteem and social interactions. Only one community study has piloted the use of MSC for self-harm scarring. Methods and analysis: We describe an acceptability and feasibility pilot randomised controlled trial; the first to examine MSC for women prisoners who self-harm. We aim to randomise 20–25 women prisoners to a 6-week MSC intervention and 20–25 to a waitlist control (to receive the MSC after the study period). We aim to train at least 6–10 long-term prisoners with personal experience of self-harm to deliver the intervention. Before and after intervention, we will pilot collection of women-centred outcomes, including quality of life, well-being and self-esteem. We will pilot collection of self-harm incidents during the intervention, resources used to manage/treat self-harm and follow-up of women at 12 weeks from baseline. Data on recruitment, retention and dropout will be recorded. We aim for the acceptability of the intervention to prison staff and women prisoners to be explored in qualitative interviews and focus groups. Ethics and dissemination: Ethical approval for COVER has been granted by the North East–York Research Ethics Committee (REC) for phases 1 and 2 (reference: 16/NE/0030) and West of Scotland REC 3 for phases 3 and 4 (reference: 16/WS/0155). Informed consent will be the primary consideration; it will be made clear that participation will have no effect on life in prison or eligibility for parole. Due to the nature of the study, disclosures of serious self-harm may need to be reported to prison officials. We aim for findings to be disseminated via events at the study prison, presentations at national/international conferences, journal publications, prison governor meetings and university/National Health Service trust communications. Trial registration number: NCT02638974 ; Pre-results.